HUBUNGAN KEPATUHAN ANTENATAL CARE DENGAN KEJADIAN KOMPLIKASI OBSTETRI PADA IBU HAMIL RISIKO TINGGI DI PUSKESMAS PASEAN PAMEKASAN - Miftahul Khairoh; Arkha Rosyaria Badrus (Jurnal Medicare, 2025)
Background: Antenatal Care (ANC) is a healthcare service aimed at monitoring maternal and fetal conditions during pregnancy and detecting risk factors and obstetric complications at an early stage. Compliance with ANC visits among high-risk pregnant women plays an important role in preventing complications that may endanger both the mother and fetus. Objective: This study aimed to analyze the relationship between Antenatal Care compliance and the incidence of obstetric complications among high-risk pregnant women. Methods: This study employed a quantitative analytical design with a cross-sectional approach. The sample consisted of 40 high-risk pregnant women selected using a total sampling technique. The independent variable was Antenatal Care compliance, while the dependent variable was the incidence of obstetric complications. Data were collected from medical records and observation sheets and analyzed using the Chi-Square test with a significance level of α = 0.05. Results: The results showed that most respondents were compliant with ANC visits, accounting for 24 respondents (60.0%), while 16 respondents (40.0%) were non-compliant. A total of 14 respondents (35.0%) experienced obstetric complications, while 26 respondents (65.0%) did not. Bivariate analysis revealed a significant relationship between ANC compliance and the incidence of obstetric complications among high-risk pregnant women (p = 0.018). Pregnant women who were non-compliant with ANC visits had a higher tendency to experience obstetric complications compared to those who were compliant. Conclusion: Antenatal Care compliance is associated with the incidence of obstetric complications among high-risk pregnant women. Improving ANC compliance through education, monitoring, and assistance by healthcare providers is essential to reduce the risk of pregnancy complications.